Positivity of BRCA 1 & 2 Mutations in Ovarian Cancer - Piryanka Goindani, Ghulam Haider, Ammara, Faiza Mahar, Ahra Sami, Perah Manzoor, Monika Bai (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: Ovarian cancer is a significant gynecological malignancy, with mutations in BRCA1 and BRCA2 genes contributing to its development and progression. Methods: This descriptive cross-sectional study was conducted at JPMC Hospital, Karachi, over six months. It involved 159 women aged 18 to 75 years with histopathologically confirmed ovarian cancer. The study employed non-probability consecutive sampling and next-generation sequencing to identify BRCA mutations. Results: The study found a low percentage of participants with a family history of ovarian cancer, a few identified with BRCA1 mutations, none with BRCA2 alone, and a minor proportion with mutations in both genes, suggesting a higher incidence of non-mutation- associated ovarian cancer. Conclusion: The findings indicate a relatively low rate of BRCA1 and BRCA2 variations within those suffering from ovarian cancer in Pakistan, pointing to the need for further research to understand the genetic underpinning of ovarian carcinoma in this population and to develop targeted prevention and treatment strategies. Keywords: BRCA mutations, ovarian cancer, genetic testing, Pakistan, prevalence, cross- sectional study.